A Discussion on Affordable Housing Projects; Case Study Mehr Housing, Iran - MARYAM GHASEMI; NAZIFE OZAY (Journal of Contemporary Urban Affairs, 2018)
Housing is one of the basic needs of humans. Families in different countries with various cultures, who have different lifestyles respond to their individual needs including physical and mental in a safe place that is called house. The world population is increasing day by day. In parallel to this population growth, housing demand increases rapidly.  Iran is also a country, which has a rapid population growth and has developed a series of policies to solve the housing problems. Affordable housing is one of solution for providing the house by governments. These type of houses is the ways to answer the demand for low-income people or the people that their income is not sufficient to the owner a house. Since 2007, the government has built a new type of affordable housing in different cities of Iran. These houses are named as Mehr Housing, which is generally medium and high-rise buildings for low-income people. In this study, it is intended to make an evaluation of the strengthens and weaknesses of Mehr Housing projects in Iran in terms of housing quality. These analyses are mainly done based on location and accessibility, safety and security, public open spaces and recreational activities, plan layout of housing units and physical features. By this discussion, it is expected to create a guide for the policymakers, designers, users and other shareholders.